"أثر مستوى الإفصاح المحاسبي عن الاستدامة على قيمة البنك -دراسة تطبيقية - " - منال, بوكنة; منال, شنوف; خلود, خنوفة; إيمان, صوالح محمد (University of eloued جامعة الوادي, 2021)
يهدف هذا البحث إلى دراسة أثر الافصاح على الاستدامة على قيمة البنك. لبلوغ هذا الهدف تم الاعتماد على منهج دراسة الحالة لدراسة حالة 12 بنك عامل في بورصة قطر وهي البنوك المفصحة عن الاستدامة في موقع بورصة قطر وموقع منصة الاستدامة للبورصة وتم اسقاط الدراسة عليهم خلال فترة المحددة (من 2017 إلى 2020). تم ذلك باستخدام اداتين لجمع البيانات هما تحليل الاحصائيات وتحليل محتوى، وبالاستعانة بالعديد من الاساليب الاحصائية لتحديد طبيعة البيانات وإنجاز الاختبارات المناسبة لكل فرضية. لقد أشارت نتائج التحليل إلى وجود ارتباط معنوي بين الافصاح على الاستدامة وقيمة البنك, إلا أنه لا توجد علاقة كبيرة بين المتغيرين الافصاح المحاسبي على الاستدامة وقيمة البنك وأن قيمة البنك تتأثر بنسبة قليلة بمعلومات المحور الاجتماعي فقط.This research aims to study the impact of disclosure on sustainability on the value of the bank. To achieve this goal, the case study method was relied on to study the case of 12 banks operating in the Qatar Stock Exchange, which are the banks that disclose sustainability on the Qatar Stock Exchange website and the Stock Exchange’s sustainability platform website, and the study was dropped on them during the specified period (from 2017 to 2020). This was done using two tools for data collection, stats analysis and content analysis, and with the help of many statistical methods to determine the nature of the data and complete the appropriate tests for each hypothesis. The results of the analysis indicated that there is a significant correlation between the disclosure on sustainability and the value of the bank, but there is no significant relationship between the two variables and that the value of the bank is affected by a small percentage only with the information of the social axis
ماستر محاسبة
Keywords: الإفصاح عن الاستدامة, الإفصاح المحاسبي, تقارير الاستدامة, قيمة البنك, بورصة قطر.; sustainability disclosure, accounting disclosure, sustainability reports, bank value, Qatar Stock Exchange